Presence and influence in lobbying: Evidence from Dodd-Frank. (14th February 2019) - Ban, Pamela; You, Hye Young
Abstract: Interest groups face many choices when lobbying: when, who, and how to lobby. We study interest group lobbying across two stages of regulatory policymaking: the congressional and agency rulemaking stages. We investigate how the Securities and Exchange Commission responds to interest groups at the end of these stages using a new, comprehensive lobbying dataset on the Dodd-Frank Act. Our approach examines citations in the SEC's final rules which reference and acknowledge the lobbying activities of specific interest groups. We find that more than 2, 900 organizations engaged in different types of lobbying activities either during the congressional bill stage, the agency rulemaking stage, or both. Meetings with the SEC and hiring former SEC employees are strongly associated with the citation of an organization in a final rule. Comments submitted by trade associations and members of Congress are cited more in a final rule compared to other organizations. While there is more variety in the types of organizations who lobby the bureaucracy than those who lobby Congress, presence does not necessarily lead to recognition or influence.